Effect of Chloroquine on Type 2 Inflammatory Response in MC903-Induced Atopic Dermatitis Mice - Wei M; Yang H; Shao Z; Wan H; Wang Y; Chen W (Dove Medical Press, 2024)
Mingjing Wei,* Huixue Yang,* Zhengchao Shao, Haoyue Wan, Yiheng Wang, Wenqi Chen Department of Dermatology, Nanjing First Hospital, Nanjing Medical University, Nanjing, Jiangsu, 210000, People's Republic of China*These authors contributed equally to this workCorrespondence: Wenqi Chen, Department of dermatology, Nanjing First Hospital, Nanjing Medical University, Changle Road 68, Nanjing, Jiangsu, 210000, People's Republic of China, Tel +8615261008432, Email WenqiChen0809@163.comIntroduction: Atopic dermatitis (AD) is a chronic, non-infectious inflammatory dermatosis. Chloroquine (CQ) has long been proven to possess anti-inflammatory properties.Objective: This paper aims to investigate the impact of CQ on type 2 inflammatory response in MC903-induced AD mice.Methods: An AD mouse model was established via MC903 induction. After CQ treatment, AD mice were intraperitoneally injected with polyinosinic: polycyclic acid [poly (I:C)] or Nigericin. Dermatitis severity was scored, and the thickness of the left ear was measured. The pathological changes in mouse skin tissues were observed by H&E staining. The number of mast cells was counted via TB staining. The content of peripheral blood T-helper 2 (Th2) cells and levels of immunoglobulin E (IgE), thymic stromal-derived lymphopoietin (TSLP), interleukin (IL)-4, IL-13, interferon (IFN)-γ, IL-1β, and IL-18 were assessed by flow cytometry and ELISA. The levels of toll-like receptor 3 (TLR3), NLRP3, ASC, and cleaved caspase-1 proteins in skin tissues were determined by Western blot.Results: CQ treatment abated dermatitis severity and left ear thickness in AD mice, alleviated skin damage, reduced mast cell number, diminished IgE, TSLP, IL-4, and IL-13 levels, and peripheral blood Th2 cell content, with no significant changes in IFN-γ level. CQ alleviated type 2 inflammatory response in AD mice by inhibiting the activation of TLR3. CQ suppressed NLRP3 inflammasome activation. Activating TLR3/NLRP3 annulled CQ-mediated alleviation on type 2 inflammatory response in AD mice.Conclusion: CQ alleviated type 2 inflammatory response in AD mice by inhibiting TLR3 activation and NLRP3 inflammasome activation.Keywords: atopic dermatitis, chloroquine, toll-like receptor 3, NLRP3 inflammasome, type 2 inflammation, MC903